Temporal and Spatial Evolution Characteristics of Meteorological Drought in the Loess Plateau from 1961 to 2020 - LI Mengting; LI Chunguang (Renmin Zhujiang)
Based on the daily meteorological data of 61 meteorological stations in the Loess Plateau from 1961 to 2020,this paper explores the historical arid evolution characteristics of the study area.The paper adopts the standardized precipitation evapotranspiration index (SPEI),Morlet wavelet analysis,drought area coverage,drought frequency,and Mann-Kendall mutation test to reveal the characteristics of dry and wet changes and cycle characteristics of the Loess Plateau under the background of nearly 60a global warming.Meanwhile,it carries out the attribution analysis of drought.The results show that the alternating wet and dry variation of SPEI values is region-wide.Annual SPEI_12 and spring,autumn,and winter SPEI_3 show a decreasing trend year by year during the study period,and the decreasing trend of drought tendency is ranked as autumn>spring>winter>annual.Summer SPEI_3 shows a relatively flat increasing trend with a trend rate of 0.02/10a.The overall drought coverage area shows an upward trend,and the annual drought frequency is between 31.40% and 35.15%.The aridification trend of the central and western regions is large.The cycle of dry and wet changes at different time scales is unstable,and it is currently in the stage of warm and humidification for a long time.The current trend of warming and humidification is only reflected in quantitative changes,which is not enough to change the basic climatic state of the region and is still in the arid and semi-arid climate range of cool and dry.